Design and implementation of DSP-based intelligent controller for automobile braking system - Sidek, Shahrul Na'im; Salami, Momoh Jimoh Emiyoka (IIUM Press, 2001)
An intelligent braking system has great potential applications especially , in developed countries where research on smart vehicle and intelligent highways are receiving ample attention. The system when integrated with other subsystems like automatic traction control, intelligent throttle , and auto cruise systems, etc will result in smart vehicle manoeuvring. The driver at the end of the day will become the passenger, safety accorded the highest priority and the journey optimized in term of time duration, cost, efficiency and comfortability. The impact of such design and development will cater for the need of contemporary society that aspires to a quality drive as well as to accommodate the advancement of technology especially in the area of smart sensors and actuators. The emergence of digital signal processor enhances the capacity and features of universal micro controller. This paper introduces the use of TI DSP, TMS320KF2407 as an engine of the system. The overall system is designed so that the value on inter-vehicle distance from infra-red laser sensor and speed of follower car from speedometer are fed into the DSP for processing, resulting in the DSP issuing commands to the actuator to function appropriately.